GAYA KEPEMIMPINAN DAN DISIPLIN: DUA FAKTOR KUNCI DI BALIK KINERJA KARYAWAN [LEADERSHIP STYLE AND DISCIPLINE: TWO KEY FACTORS BEHIND EMPLOYEE PERFORMANCE] - Hanis, Umar (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to understand the meaning of the role of leadership style and work discipline in shaping employee performance at PT Galaksi Medika Perkasa, South Bekasi. The research employed an associative approach involving 60 employees as the research sample, all of whom were surveyed through a questionnaire. Data analysis was conducted using multiple regression to examine the relationships among variables in a comprehensive manner. The findings indicate that leadership style plays a strategic role in enhancing employee performance, particularly through leaders’ ability to provide clear direction, demonstrate role modeling, and offer support to employees in carrying out their tasks. Effective leadership is shown to foster motivation, a sense of responsibility, and work commitment, thereby encouraging employees to achieve more optimal performance. In addition, work discipline is interpreted as a fundamental factor supporting performance, as adherence to rules, punctuality, and consistency at work create order and efficiency in task execution. Simultaneously, the results of the multiple regression analysis confirm that leadership style and work discipline complement each other in shaping employee performance, where strong leadership yields a greater impact when supported by high levels of work discipline. These findings suggest that improving employee performance depends not only on individual capabilities but also on the quality of leadership and the consistent enforcement of work discipline within the organization.